1995
DOI: 10.1007/bf00128504
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic properties of HIV-1 protease produced by total chemical synthesis with cysteine residues replaced by isosteric L-?-amino-n-butyric acid

Abstract: Human immunodeficiency virus-I protease, produced by total chemical synthesis with the cysteine residues replaced by L-a-amino-n-butyric acid ([Aba 67' 95] HIV-1 PR), has been used extensively for the X-ray crystallographic structural analysis of the enzyme and its complexes utilized in drug design. Here we report kinetic studies on the synthetic enzyme. The pH optimum is 5.5 at ionic strengths of 0.1 and 1.0. The acid pH optimum is due to a decrease in binding affinity at higher pH values rather than to a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The two cysteine residues (Cys67 and Cys95) of the native sequence were replaced with the isosteric analogue L-Ramino-n-butyric acid (Aba) for ease of synthesis and handling to yield [Aba 67,95 ]HIVPR (7). This enzyme was fully active and had the same kinetic properties as the cloned enzyme (19). [Aba 67,95 ]HIVPR, which we refer to as HIVPR, was used in the HIVPR-1 cocrystallization experiment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two cysteine residues (Cys67 and Cys95) of the native sequence were replaced with the isosteric analogue L-Ramino-n-butyric acid (Aba) for ease of synthesis and handling to yield [Aba 67,95 ]HIVPR (7). This enzyme was fully active and had the same kinetic properties as the cloned enzyme (19). [Aba 67,95 ]HIVPR, which we refer to as HIVPR, was used in the HIVPR-1 cocrystallization experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of the macrocyclic peptidomimetic inhibitors was carried out as described previously ( ). [Aba 67,95 ]HIVPR (SF2 isolate) and [Aba 67,95 ]HIVKI were chemically synthesized in our laboratories by solid phase peptide synthesis ( , ). The two cysteine residues (Cys67 and Cys95) of the native sequence were replaced with the isosteric analogue l -α-amino- n -butyric acid (Aba) for ease of synthesis and handling to yield [Aba 67,95 ]HIVPR ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Side chain protection of appropriate lysine DMSO in the assay was only 1% (v/v). It has been reported that DMSO concentrations õ2% have little efresidues with a base labile fluorenylmethoxycarbonly group during peptide synthesis permitted their selec-fect on the catalytic efficiency of the HIV PR (18). It has been reported that Abz derivatives in which the tive deprotection (2 1 20% v/v piperidine in DMF for 5 min) for reaction with HBTU-activated 2-aminobenzoic Abz group is attached to the epsilon amine of a lysine…”
Section: Peptide Synthesis and Purificationmentioning
confidence: 99%
“…Table reports inhibitor potencies of some molecules containing the macrocyclic mimetic of Phe-Ile-Val against synthetic HIVPR in vitro. Under the assay conditions, reference inhibitors JG365 3 and DM323 potently inhibit cleavage of a synthetic fluorogenic substrate . The larger 16-membered ring in 5 was no more effective than the 15-membered ring of 4 , and neither ring on its own was a significant inhibitor (IC 50 ∼ 1−10 μM).…”
mentioning
confidence: 99%